Impact of acute and chronic inhalation exposure to CdO nanoparticles on mice - Lebedová, J; Bláhová, L; Večeřa, Z; Mikuška, P; Dočekal, B; Buchtová, M; Míšek, I; Dumková, J; Hampl, A; Hilscherová, K (Environmental science and pollution research international, 2016)
Cadmium nanoparticles can represent a risk in both industrial and environmental settings, but there is little knowledge on the impacts of their inhalation, especially concerning longer-term exposures. In this study, mice were exposed to cadmium oxide (CdO) nanoparticles in whole body inhalation chambers for 4 to 72 h in acute and 1 to 13 weeks (24 h/day, 7 days/week) in chronic exposure to investigate the dynamics of nanoparticle uptake and effects. In the acute experiment, mice were exposed to 2.95 × 106 particles/cm3 (31.7 μg CdO/m3). The same concentration and a lower one (1.18 × 106 particles/cm3, 12.7 μg CdO/m3) were used for the chronic exposure. Transmission electron microscopy documented distribution of nanoparticles into all studied organs. Major portion of nanoparticles was retained in the lung, but longer exposure led to a greater relative redistribution into secondary organs, namely the kidney, and also the liver and spleen. Accumulation of Cd in the lung and liver occurred already after 24 h and in the brain, kidney, and spleen after 72 h of exposure, and a further increase of Cd levels was observed throughout the chronic exposure. There were significant differences in both Cd accumulation and effects between the two exposure doses. Lung weight in the higher exposure group increased up to 2-fold compared to the control. Histological analyses showed dose-dependent alterations in lung and liver morphology and damage to their tissue. Modulation of oxidative stress parameters including glutathione levels and increased lipid peroxidation occurred mainly after the greater chronic exposure. The results emphasize risk of longer-term inhalation of cadmium nanoparticles, since adverse effects occurring after shorter exposures gradually progressed with a longer exposure duration.
Keywords: Mice, Inbred ICR; Liver; játra; oxidy; Nanoparticles; Glutathione; Oxides; Oxidative Stress; Mice; Lipid Peroxidation; Tissue damage; Cadmium; Lipid peroxidation; sloučeniny kadmia; ženské pohlaví; Nanoparticle; zvířata; plíce; myši inbrední ICR; glutathion; Oxidative stress; ledviny; Cadmium Compounds; nanočástice; myši; inhalační expozice; oxidační stres; Inhalation Exposure; Kidney; Female; Lung; peroxidace lipidů; Accumulation; Animals